Analysis of the Demand for Continuing Education of Nurses in the Department of Infectious Diseases and Its Influencing Factors. (6th September 2022) - Pang, Xiaoqun; Zhang, Meiling; Pang, Huiyan
Abstract : Infection department is unique in working hours, environment, content, methods, and skills requirements, and continuing education plays an important role in stabilizing and improving the professional level of nurses in the infection department. Understanding the needs of nurses in the infection department for continuing education and the possible influencing factors of participating in continuing education and providing a management basis for managers in a targeted way can make the role of continuing education fully play. In this study, according to the characteristics of the Department of Infection, a questionnaire was designed to investigate the continuing education needs of nursing staff in the Department of Infection and analyze the influencing factors. The results show that the nursing staff in the infection department had a greater demand for continuing education. Age, professional title, working life, hospital level, and marital status were the risk factors that affected their demand for continuing education.